Evaluation of the role of perceived quality and satisfaction of beneficiaries about the health care services and benefits of community clinics in Bangladesh - Talukder, Shamim Hayder; Akter, Shahin; Dina Farhana,; Salahin, Kazi Fayzus; Khanam, Shirin; Rahman, Md. Mostafizur; Hossain, Md Saddam; Islam, Tasneem; Sultana, Ummay Farihin; Prodhan, Tasbirul Islam; Islam, Sheikh Mohammed Shariful (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Introduction Bangladesh provides free healthcare to its citizens through 10,723 community clinics which provide one-stop healthcare services that is vital in ensuring primary healthcare. Measuring beneficiary' contentment is crucial to improve the quality of care and the perceived service quality have a significant impact on how often people use those health services. This study focuses on perceived quality and satisfaction of beneficiaries about the primary health care services and benefits of community clinics in Bangladesh. Methods A quantitative descriptive survey was conducted from March 2019 to April 2019 in the catchment area of 80 community clinics located at 16 Upazila under eight districts of eight divisions in Bangladesh. The survey compiled local data on client’s experience on health care service of community clinics. Besides, Sixteen Upazilas from eight districts were randomly selected for conducting interviews. Results Data was provided by a total of 760 female participants, among them majority (41%) belonged to the age group of 18-24 years old, and this very group showed more satisfaction than others (Odds Ratio 1.44). Besides, childless married women were also found to be content with the community clinic services compared to the remaining types of clients (Odds Ratio 1.64). However, gender, education, and economic perspective were positive aspects of getting service from community clinics. Conclusions Although there is a challenge balancing psychosocial and medical care, promoting client-oriented care with a focus on the cultural factors of the area is vital. This can be done through community-focused training together with explaining written prescriptions to the beneficiary, including the signs, symptoms, treatment, and referral points. The study findings will enable responsible authority to improve quality of primary health care services, realizing beneficiary’ ideas of community clinic service quality.